Physicochemical Impacts of Dust Storms on Aerosol and Glacier Meltwater on the Northern Margin of the Taklimakan Desert - Zheng, Cunying; Li, Zhongqin; Zhou, Ping; Zhang, Xin; Zhou, Xi; Ma, Shan (Frontiers in Earth Science, 2021)
To analyze the impacts of dust storms on the atmospheric environment and meltwater environment, intensive and simultaneous sampling for aerosols and meltwater on the terminal moraine (41°73′ N, 79°88′ E, 3789 m a.s.l.) of Qingbingtan Glacier No. 72 (Glacier No. 72) on the northern margin of the Taklamakan Desert (TD) were conducted during the summer of 2008. Aerosol and meltwater chemistry (including the species of Na+, K+, Mg2+, Ca2+, NH4+, Cl-, SO42- and NO3-) was analyzed by ion chromatography. The results indicated that the major anions and cations in the samples were SO42- and Ca2+, respectively. In the dust event, the average value of aerosol ions was 566.91 neq·m-3, which is nearly 5 times that under nondust conditions (115.58 neq·m-3). In addition, in the meltwater samples, the sum of ion concentrations ranged from 31.26 to 180.98 mg·L-1, with an average of 76.40 mg·L-1. When a dust storm occurred, the ion concentrations in these two media increased significantly and simultaneously, but with different trends due to the different influencing factors. That is, the atmospheric environment was significantly affected by the dust storm, but the main influence on the water environment was the temperature change instead of the dust storm itself. According to the correlation analysis and principal component analysis, the water-soluble ions, such as Ca2+, Mg2+, Na+, K+, Cl－and SO42-, originated from natural sources, while NO3- and NH4+ originated from anthropogenic sources. The results of the air mass trajectory suggested that the regional dust storms caused by the air masses originating from Eastern Europe and Siberia had a significant influence on the glacial environment.